Innovation paths in wind power: insights from Denmark and Germany - Rasmus Lema; Frauke Urban; Johan Nordensvard; Wilfried Lütkenhorst (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Denmark and Germany both make substantial investments in low carbon innovation, not least in the wind power sector. These investments in wind energy are driven by the twin objectives of reducing carbon emissions and building up international competitive advantage. Support for wind power dates back to the 1970s, but it has gained particular traction in recent years thus opening up new innovation paths. This paper explores the key features, similarities and differences in innovation paths in Denmark and Germany and sheds light on their main determinants. The paper shows that there are many commonalities between Denmark and Germany when it comes to innovation pathways, both in technological and organisational innovation. In turbine technology, the similarities are the constant increase in turbine size and quality. The key difference to be found is the relative importance of different turbine designs. The `Danish Design' remains the global standard. The direct drive design, while uncommon in Denmark, dominates the German installation base. Direct drive technology has thus emerged as a distinctly German design and sub-trajectory within the overall technological innovation path. When it comes to organising wind turbine deployment, both countries have moved along broadly similar paths. There are now fewer turbines deployed than at any time in the past 10 to 20 years, but on average these are concentrated in larger projects and the production capacity and total electricity output has increased significantly in both countries. The key difference is in the role of the offshore segment in deployment: Denmark has been a pioneer in the offshore segment, which has hitherto played a much smaller role in Germany. While this paper shows that there are many common features between the two countries, it also identifies a diversity of pathways, or rather, a co-existence of different sub-trajectories in both core technology and in the organisation of deployment. It is as yet unclear whether the future will bring more convergence or divergence. To address this, the paper explores specific determinants of innovation paths: government policies, demand conditions, geography, value chains, and the strategies undertaken by firms. It demonstrates that the innovation paths common to both countries have roots in a confluence of determining factors which are mainly due to social and political priorities, preferences and decisions at national level. However, the sub-trajectories, which create variation between Denmark and Germany, differ in this regard. They tend to have roots in `given' geographical conditions and in company-level technology choices. In other words, many of the similarities in innovation paths between Denmark and Germany have common national causes, while company-specific strategies also influence the innovation paths in significant ways. This raises important questions about the national specificity of innovation paths in wind power development. Finally, the paper briefly addresses the increasing global interconnectedness of wind technology markets and the role of emerging new players, such as China and India.
Keywords: 330; Energie; Technology and innovation